1991
DOI: 10.1159/000182160
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Thyroid Function in Early and Late Pregnancy<sup>1</sup>

Abstract: Thyroid function was investigated during and after pregnancy in 12 healthy euthyroid women. During pregnancy, serum total T4 (TT4) levels were significantly elevated and nearly stable, while thyroxine-binding globulin (TBG) levels progressively increased till the 7th month. A slight elevation, though not significant, of free T4 (fT4) was recorded in early pregnancy. In the following months, fT4, free T3 (fT3) and the T4/TBG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
0
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 24 publications
2
0
0
1
Order By: Relevance
“…TT 4 levels during pregnancy have been well studied both in countries with iodine sufficiency and iodine insufficiency and their values generally plateau during the second and third trimester at about 150% of their prepregnancy values (3,4,6,7,10,11,(37)(38)(39). The magnitude of the increase in this study was similar to that reported in previous studies.…”
Section: Discussionsupporting
confidence: 88%
“…TT 4 levels during pregnancy have been well studied both in countries with iodine sufficiency and iodine insufficiency and their values generally plateau during the second and third trimester at about 150% of their prepregnancy values (3,4,6,7,10,11,(37)(38)(39). The magnitude of the increase in this study was similar to that reported in previous studies.…”
Section: Discussionsupporting
confidence: 88%
“…3) which have been observed throughout the last 4 days of pregnancy may indicate an increase in maternal metabolism to provide the necessary physiological requirements for the crucial task of parturition as well as setting the stage for the initiation of lactation. Our results are in accord with previous clinical observations which have been noted in other mammalian species 16,17,18 . Moreover, an increase in estrogen levels during late pregnancy is associated with an increase in total serum T4 levels in ewes 15 .…”
Section: Resultssupporting
confidence: 93%
“…Причем у 20% беременных от мечаются субнормальные значения ТТГ [38,40,80]. Высокий уровень обладающего тиреостимулиру ющим эффектом ХГ [54,76,100] порой определяет повышенные концентрации св. Т4 в первом тримес тре беременности [38,40,80].…”
Section: индивидуальная вариабельность уровня ттг и тиреоидных гормоновunclassified